Gender and Sociocultural Disparities in Dyslipidemia: A Cross-Sectional Study in South Waziristan, Khyber Pakhtunkhwa, Pakistan - Rehman, Sana; Shah, Aown Haider; Rab Nawaz,; Hashmi, Samreen; Rashid, Areeba; Saeed, Asma; Khan, Muhammad Asghar; Rashid, Areesha (Indus Journal of Bioscience Research, 2025)
Background: Dyslipidemia, abnormal levels of cholesterol & lipids, is a major cause of heart disease and can vary widely due to gender, lifestyle, and access to healthcare, especially in remote areas. Objective: The primary objective of this study was to examine gender and sociocultural differences in Dyslipidemia among patients from South Waziristan, Khyber Pakhtunkhwa, Pakistan. Methods: A cross-sectional study was conducted among 104 patients from South Waziristan. Lipid profiles including LDL, TC, TG, and HDL were measured. Data were statistically analyzed and its significance was compared with p<0.0001 to explore differences by gender, age group, caste, diabetes status, and physical activity levels. Results: A substantial difference of Dyslipidemia between male and female participants was observed. Data revealed that women of age group 46–60 presented increased LDL at 216 mg/dL and TC at 262 mg/dL than male levels (LDL 97 mg/dL and TC 179 mg/dL respectively). The Wazir caste population showed increased levels of LDL and TG which were most pronounced in their female population. Females who did not exercise regularly presented the highest LDL levels while diabetic females showed below-average HDL (42 mg/dL vs. 55 mg/dL) together with LDL results (81 mg/dL vs. 135 mg/dL) than non-diabetic female subjects. Conclusion: Females, particularly postmenopausal women exhibit elevated levels of LDL and total cholesterol, with lifestyle factors and caste characteristics also influencing lipid profiles. These findings underscore the need for targeted, gender and culture-specific interventions in South Waziristan.